Assessment of the plasma disappearance of cholyl'l14C-glycine as a test of hepatocellular disease. Issue 9 (September 1977) - Thjodleifsson, B; Barnes, S; Chitranukroh, A; Billing, B H; Sherlock, S
Abstract : The plasma disappearance of a tracer dose of cholyl-l14C-glycine has been examined in 12 control subjects and in 32 patients with hepatocellular dysfunction. Simple analysis of the data did not detect hepatic dysfunction except in severe hepatocellular disease. The greatest degree of discrimination between normal subjects and patients with mild liver disease was obtained by taking the ratio of the plasma retention at 60 minutes to that at 10 minutes; it was similar to that obtained with serum gamma-glutamyl transferase. The two hour post-prandial plasma "total" bile acid concentration gave complete separation between the control subjects and patients with liver disease.